How do people with physical disabilities want to construct virtual identities with avatars? - Park, Jaeyoung; Kim, Seongcheol (Frontiers in Psychology, 2022)
In the virtual world, people can reconstruct their identity the way they want with avatars. Thus, the high degree of freedom in avatar customization will give new chances to socially marginalized people (e.g., females, non-whites) experiencing discrimination against their physical traits. However, previous studies found that female and non-white avatars were still in the minority in the virtual world, even excluding people with disability from the discourse. It means that there should be more efforts to make the virtual world inclusive beyond technical support. This paper explores the shared perception of avatar-based disability representations among people with disability to help understand how the disabled want to construct their identity with avatars. The study also gives direction for a barrier-free virtual world. We conducted in-depth interviews with people with physical impairments who used virtual world services and performed a core-periphery analysis of social representations. This study expands the range of academic adoption of the social representations theory and provides insights for stakeholders such as policymakers to design an inclusive virtual world.